Immunogenicity and protective efficacy of a live, oral cholera vaccine formulation stored outside-the-cold-chain for 140 days - Xian, Tew Hui (BMC Immunol, 2020)
BACKGROUND: Cholera, an acute watery diarrhoeal disease caused by Vibrio cholerae serogroup O1 and O139 across the continents. Replacing the existing WHO licensed killed multiple-dose oral cholera vaccines that demand ‘cold chain supply’ at 2–8 °C with a live, single-dose and cold chain-free vaccine would relieve the significant bottlenecks and cost determinants in cholera vaccination campaigns. In this direction, a prototype cold chain-free live attenuated cholera vaccine formulation (LACV) was developed against the toxigenic wild-type (WT) V. cholerae O139 serogroup. LACV was found stable and retained its viability (5 × 10(6) CFU/mL), purity and potency at room temperature (25 °C ± 2 °C, and 60% ± 5% relative humidity) for 140 days in contrast to all the existing WHO licensed cold-chain supply (2–8 °C) dependent killed oral cholera vaccines. RESULTS: The LACV was evaluated for its colonization potential, reactogenicity, immunogenicity and protective efficacy in animal models after its storage at room temperature for 140 days. In suckling mice colonization assay, the LACV recorded the highest recovery of (7.2 × 10(7) CFU/mL) compared to those of unformulated VCUSM14P (5.6 × 10(7) CFU/mL) and the WT O139 strain (3.5 × 10(7) CFU/mL). The LACV showed no reactogenicity even at an inoculation dose of 10(4)–10(6) CFU/mL in a rabbit ileal loop model. The rabbits vaccinated with the LACV or unformulated VCUSM14P survived a challenge with WT O139 and showed no signs of diarrhoea or death in the reversible intestinal tie adult rabbit diarrhoea (RITARD) model. Vaccinated rabbits recorded a 275-fold increase in anti-CT IgG and a 15-fold increase in anti-CT IgA antibodies compared to those of rabbits vaccinated with unformulated VCUSM14P. Vibriocidal antibodies were increased by 31-fold with the LACV and 14-fold with unformulated VCUSM14P. CONCLUSION: The vaccine formulation mimics a natural infection, is non-reactogenic and highly immunogenic in vivo and protects animals from lethal wild-type V. cholerae O139 challenge. The single dose LACV formulation was found to be stable at room temperature (25 ± 2 °C) for 140 days and it would result in significant cost savings during mass cholera vaccination campaigns.